Usability of Chronic Kidney Diseases Electronic-Health Information: A Systematic Review - Ira Suarilah; Wahyuni Tri Lestari; Rini Purwanti (Universitas Airlangga, 2023)
Background: Information on chronic kidney disease is easily accessible in a variety of digital formats and is posted in health information resources, electronic health, or eHealth. In that it can enable people with chronic kidney disease to manage their condition, the field of eHealth is promising. Aims: The purpose of this study is to evaluate the usability of eHealth in the treatment of chronic kidney disease by critically analyzing the published papers in this area. Methods: The following databases were searched systematically: The following databases were thoroughly searched: EBSCO, CINAHL, ProQuest, MEDLINE, PubMed, Cochrane, and Google Scholar. Eight studies looked into the specific impact of eHealth on chronic kidney disease. These studies addressed a variety of subjects, including the user, healthcare professionals, and system bonding, mobile eHealth, content, and eHealth evaluation on chronic kidney disease. Results: There is a knowledge gap in the field of eHealth for chronic kidney disease. The findings reveal a significant disparity in the terminology and conceptualizations used in eHealth information on chronic kidney disease. The availability of eHealth information on chronic kidney disease that prioritizes patient education, behavior modification, and prevention has led to inconsistent usage. Lack of sufficient data may hinder the development of eHealth interventions for people with chronic kidney disease. Conclusion: This study emphasizes the urgent need for content acceptance and access as well as evaluation that is evidence-based for the conceptualization of eHealth for chronic kidney disease.